2013
DOI: 10.1038/aps.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits the adhesion and migration of BCG823 gastric cancer cells by affecting the structure and function of the vasodilator-stimulated phosphoprotein (VASP)

Abstract: Aim: Vasodilator-stimulated phosphoprotein (VASP) expression is upregulated in human cancers and correlates with more invasive advanced tumor stages. The aim of this study was to elucidate the mechanisms by which matrine, an alkaloid derived from Sophora species plants, acted on the VASP protein in human gastric cancer cells in vitro. Methods: VASP was expressed and purified. Intrinsic fluorescence spectroscopy was used to study the binding of matrine to VASP. CD spectroscopy was used to examine the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…VASP protein was expressed in E. coli Rosetta by induction with 0.5 mM isopropyl-1-thio-β-D-galactopyranoside (IPTG) at 18°C for 16 h as previously described [51, 52]. The intrinsic fluorescence spectroscopy was used to investigate the interaction between berberine with VASP at 25°C by LS-55 luminescence spectrometer (Perkin-Elmer Life Sciences, Shelton, CT).…”
Section: Methodsmentioning
confidence: 99%
“…VASP protein was expressed in E. coli Rosetta by induction with 0.5 mM isopropyl-1-thio-β-D-galactopyranoside (IPTG) at 18°C for 16 h as previously described [51, 52]. The intrinsic fluorescence spectroscopy was used to investigate the interaction between berberine with VASP at 25°C by LS-55 luminescence spectrometer (Perkin-Elmer Life Sciences, Shelton, CT).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several basic studies showed direct binding proteins of matrine. Epidermal growth factor receptor (Wang et al, 2010 ), vasodilator-stimulated phosphoprotein (Zhang et al, 2013 ), and annexin A2 (Wang et al, 2017 ) were identified as the direct binding proteins of matrine in cancer cells, and matrine inhibited these protein-induced cell events. Cui et al showed that matrine bound to amyloid β peptide and receptor for advanced glycation end products, and the cell signaling stimulated by these proteins were inhibited by matrine in neuroblastoma cells (Cui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Matrine and sophoridine are quinolizidine alkaloids isolated from traditional Chinese medicine such as Sophora flavescens, Sophora subprostrata, or Sophora alopecuroides, which are tetracyclic quinolizine compounds with a molecular skeleton and can be regarded as a combination of two quinolizine rings [ 19 , 20 ]. In recent years, it has been discovered that the alkaloids of S. flavescens exhibit anti-arrhythmic, anti-inflammatory, anti-fibrosis, anti-tumor, and numerous other significant pharmacological activities, and various formulations have been widely used in clinical practice [ 21 , 22 , 23 , 24 ]. Therefore, in the present work, we used matrine and sophoridine as target drug molecule probes to study the switching properties of the binary carboxylated multi-walled carbon nanotubes/poly( N , N -diethylacrylamide) (c-MWCNTs/PDEA) film system.…”
Section: Introductionmentioning
confidence: 99%